1988
DOI: 10.1017/s0003356100003561
|View full text |Cite
|
Sign up to set email alerts
|

Rumen degradation of straw 6. Effect of polysaccharidase enzymes on degradation characteristics of ensiled rice straw

Abstract: The effects of three variables; polysaccharidase inclusion level (0, 5 and 10 g/kg), moisture content (500, 600 and 700 g/kg dry matter (DM), and particle size (20, 5 and 2 mm), on the quality and degradation characteristics of ensiled rice straw were investigated. The polysaccharidase product used was shown to contain a broad spectrum of activities against polysaccharides typical of plant material. The major activities present being: mixed link glucanase, xylanase and both endo- and exo-cellulase. The straw t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 25 publications
2
9
0
2
Order By: Relevance
“…Nakashima et al22) reported that by 0.5% and 1.0% cellulase treatments, the NDF of rice straw decreased by 9-10% as compared to that of untreated straw. In the present experiment the NDF content of enzyme-treated straw also decreased slightly, but not at the same magnitude as that described by Nakashima et al 22). The reason for this was considered to be the higher DM contents of the rice straw used in the present experiment.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…Nakashima et al22) reported that by 0.5% and 1.0% cellulase treatments, the NDF of rice straw decreased by 9-10% as compared to that of untreated straw. In the present experiment the NDF content of enzyme-treated straw also decreased slightly, but not at the same magnitude as that described by Nakashima et al 22). The reason for this was considered to be the higher DM contents of the rice straw used in the present experiment.…”
Section: Methodssupporting
confidence: 82%
“…22) reported that rice straw treated with polysaccharidase (Meicelase) at levels of 5 and 10g/kg DM gave lower final pH than that of untreated straw (P<0.01). They adjusted the DM content to 50, 40 and 30% which was far lower than that of the present experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The significant negative effect of fibre on the degradation characteristics is consistent with the report by others (Ramanzin et al, 1986;Nakashima et Nakashima and Qrskov, 1989) for the corresponding untreated fractions. The difference between fractions could be a consequence of their chemical composition as well as to the different configuration of lignified cells within the respective plant tissue.…”
Section: Effect Of Fractionsupporting
confidence: 91%
“…In a similar study on fibre rich forages, Feng et al (1996), Krause et al (1998), Yang et al (1999) and Beauchemin et al (2000) observed only small increments in fibre digestion. In vitro increases in dry matter (DM) digestibility have also been reported by Nakashima et al (1988), Feng et al (1996, and Yang et al (1999).…”
Section: Introductionmentioning
confidence: 85%